Peristomal Skin Health: A WOCN Society Consensus Conference. Issue 3 (May 2021) - Ratliff, Catherine R.; Goldberg, Margaret; Jaszarowski, Kelly; McNichol, Laurie; Pittman, Joyce; Gray, Mikel
Abstract : The Wound, Ostomy, and Continence Nurses (WOCN) Society identified the need to define and promote peristomal skin health. A task force was appointed to complete a scoping literature review, to develop evidence-based statements to guide peristomal skin health best practices. Based on the findings of the scoping review, the Society convened a panel of experts to develop evidence- and consensus-based statements to guide care in promoting peristomal skin health. These consensus statements also underwent content validation using a different panel of clinicians having expertise in peristomal skin health. This article reports on the scoping review and subsequent 6 evidenced-based statements, along with the generation and validation of 19 consensus-based statements, to assist clinical decision-making related to promoting peristomal skin health in adults.